If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = t + t + -1y Combine like terms: t + t = 2t y = 2t + -1y Solving y = 2t + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. y + y = 2t + -1y + y Combine like terms: y + y = 2y 2y = 2t + -1y + y Combine like terms: -1y + y = 0 2y = 2t + 0 2y = 2t Divide each side by '2'. y = t Simplifying y = t
| 3(-40+-2r)+20= | | y-2=.10(x+10) | | 2•-4/5 | | 6-4(2x+8)=16 | | (t-3)7=6+21 | | 6x-13=90 | | 8[t-2]= | | 4v+4=4 | | 4p+1=-15 | | 4k-3(k-8)=2(3-5k)+7 | | 50-5x=80-17x | | 15y-(3-[4y+4]+57)=2-y | | 2(6-4x)=21-9x | | -7+(8z+2)=(7z+5)+1 | | 3.7+15.09= | | -1/3m=-8 | | r^2-8=26 | | Z-2=4+9x | | 4.5[h-6]= | | 19x+3=11x-2 | | 5/8j-3/4=1/2 | | .5d-3/4=3/5d | | 79-2x=88-3x | | 3y-7=4y+8 | | -1/2(6x-1/3) | | 5p^2=230 | | 9x-8=x+10 | | 5x^2+4x-48=0 | | -2=-3/5x-3 | | 5(x)=20*1.03x | | -6b+2b-5b-3b+4b=-8b | | 40n^2+36n-28=0 |